PENINGKATAN BRAND AWARENESS “BATIK LUKIS HANDMADE” MELALUI REBRANDING DAN DIGITAL MARKETING - Indriana, Nilna; Nisa’, Ida Fauziatun (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
In the Ledok Wetan sub-district, Bojonegoro district, there are UMKM that are engaged in the painted batik business, they are engaged in cloth painting, namely painting on clothes, wallets, headscarves, shoes, bags, masks, and many other cloth media. This UMKM has been established for many years but its development is still slow, this is proven by the lack of product sales and the lack of public knowledge about Batik Lukis products. By looking at the problems above, researchers feel it is important to brand Batik Lukis UMKM products and hold digital marketing training with the aim of increasing brand awareness. The method used in this community service activity is Participatory Action Research (PAR). with stages, namely, observation, planning, action, and evaluation. The results of the activity show that there is an increase in sales of painted batik products via digital and that Bojonegoro's typical painted batik products are better known to people outside Bojonegoro, they can become one of the icons and souvenirs typical of Bojonegoro, so that they can increase, improve and support the family economy.